Pathogenic roles and diagnostic utility of interleukin-18 in autoinflammatory diseases - Shimizu, Masaki; Takei, Syuji; Mori, Masaaki; Yachie, Akihiro (Frontiers in Immunology, 2022)
Interleukin (IL)-18 is a pleiotropic, pro-inflammatory cytokine involved in the regulation of innate and adaptive immune responses. IL-18 has attracted increasing attention as a key mediator in autoinflammatory diseases associated with the development of macrophage activation syndrome (MAS) including systemic juvenile idiopathic arthritis and adult-onset Still’s disease. In these diseases, dysregulation of inflammasome activity and overproduction of IL-18 might be associated with the development of MAS by inducing natural killer cell dysfunction. Serum IL-18 levels are high in patients with these diseases and therefore are useful for the diagnosis and monitoring of disease activity. In contrast, a recent study revealed the overproduction of IL-18 was present in cases of autoinflammation without susceptibility to MAS such as pyogenic sterile arthritis, pyoderma gangrenosum, and acne (PAPA) syndrome. The pathogenic and causative roles of IL-18 remain unclear in these autoinflammatory diseases. Further investigations are necessary to clarify the role of IL-18 and its importance as a therapeutic target in the pathogenesis of autoinflammatory diseases.